1982
DOI: 10.1002/cne.902060204
|View full text |Cite
|
Sign up to set email alerts
|

Origin and organization of pigment epithelial apical projections to cones in cat retina

Abstract: The apical surface of the retinal pigment epithelial cells (RPE) in the cat extend long sheetlike membranes that wrap concentrically above and around cone outer segments forming the cone sheath. The origin and organization of these sheetlike projections were studied in serial sections by electron microscopy. The apical surface of the RPE cells was found to consist of a thin zone of anastomosing ridges, or microplicae, from which longer projections extend. The lamellar projections forming the cone sheath origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

1986
1986
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…C57BL/6J mice were housed at University of California, Los Angeles and used at age 6 wk. Adult cat, Felis catus, and rhesus monkey, Macaca mulatta, tissues were from previous studies performed at University of California, Santa Barbara, and University of California, San Francisco (43,44). All animals were kept on a 12-h light/12-h dark cycle, and treated in accordance with appropriate institutional guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6J mice were housed at University of California, Los Angeles and used at age 6 wk. Adult cat, Felis catus, and rhesus monkey, Macaca mulatta, tissues were from previous studies performed at University of California, Santa Barbara, and University of California, San Francisco (43,44). All animals were kept on a 12-h light/12-h dark cycle, and treated in accordance with appropriate institutional guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were then washed in acetone and propylene oxide, and embedded in Araldite 502. Cat and monkey tissue was fixed using transcardiac perfusion, as described previously (43,44).…”
Section: Methodsmentioning
confidence: 99%
“…Hedgehog) and the transduction of environmental stimuli (mechano, chemo, and osmosensory functions) (Gerdes, 2009; Goetz, 2010). Early studies reported that adult RPE display a PC that is spatially correlated with the presence of cones in the neural retina (Fisher and Steinberg, 1982). More recent immunofluorescence analysis on mouse RPE flatmounts using antibodies against acetylated tubulin concluded that RPE PC is present in developing RPE but disappears in the mature retina (Nishiyama et al, 2002).…”
Section: Structural and Functional Polarity Of Rpe Cellsmentioning
confidence: 99%
“…The relationship with cone photoreceptors was confirmed by electron microscopy (not illustrated) in which the EAAT4-positive projections were seen to fill the supracone space and surround individual cone outer segments. Such structures have been described previously in the cat retina by Fisher and Steinberg (1982) and termed cone sheaths. Dense staining for EAAT4 was also seen in fibrous processes near the inner limiting membrane (Fig.…”
mentioning
confidence: 94%